2017
DOI: 10.1021/acs.est.7b04179
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Individual Isopropylated and tert-Butylated Triarylphosphate (ITP and TBPP) Isomers in Several Commercial Flame Retardant Mixtures and House Dust Standard Reference Material SRM 2585

Abstract: Since the phase-out of pentaBDE in the early 2000s, replacement flame-retardant mixtures including Firemaster 550 (FM 550), Firemaster 600 (FM 600), and organophosphate aryl ester technical mixtures have been increasingly used to treat polyurethane foam in residential upholstered furniture. These mixtures contain isomers of isopropylated and tert-butylated triarylphosphate esters (ITPs and TBPPs), which have similar or greater neuro- and developmental toxicity compared to BDE 47 in high-throughput assays. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
63
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 94 publications
(66 citation statements)
references
References 37 publications
(73 reference statements)
2
63
1
Order By: Relevance
“…Along with TPHP, the two ITP compounds on hand wipes were also significantly correlated with tb-PPP (r s =0.23–0.31, p<0.01). Because TPHP is a component of the TBPP mixture this association likely reflect co-exposure of the parent compounds even though TPHP is unlikely to be metabolized to tb-PPP, (Phillips et al, 2017; Van den Eede et al, 2013). The significant correlation of 2IPPDPP and 4IPPDPP with tb-PPP may also be explained by the detection of trace amounts of ITP compounds in the Firemaster® 600 and TBPP mixtures, thereby also reflecting co-exposure of the parent compounds (Phillips et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with TPHP, the two ITP compounds on hand wipes were also significantly correlated with tb-PPP (r s =0.23–0.31, p<0.01). Because TPHP is a component of the TBPP mixture this association likely reflect co-exposure of the parent compounds even though TPHP is unlikely to be metabolized to tb-PPP, (Phillips et al, 2017; Van den Eede et al, 2013). The significant correlation of 2IPPDPP and 4IPPDPP with tb-PPP may also be explained by the detection of trace amounts of ITP compounds in the Firemaster® 600 and TBPP mixtures, thereby also reflecting co-exposure of the parent compounds (Phillips et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…For aryl OPEs, this projected increase will likely be compounded by the recent Consumer Product Safety Commission (CPSC) ruling banning the use of organohalogen flame retardants in several consumer product categories in the United States (Kaye, 2017). Aryl OPEs are anticipatory substitutes for the banned organohalogen flame retardants, and are already used extensively in commerce (Phillips et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Technical IPTPP is a mixture of aryl phosphate ester congeners that vary in the number of phenyl moieties containing the isopropyl group. 4 Isopropylphenyl, diphenyl phosphate is the major congener in technical IPTPP, and its presence has been reported in indoor air from an electronics recycling plant in Sweden 5 and house dust in North Carolina. 6 In addition, several studies have identified an urinary metabolite of this congener in the majority of individuals in the United States.…”
Section: Introductionmentioning
confidence: 99%
“…9 Recent evidence shows that exposure of nonhalogenated organophosphate components increased exposure risks and lead to adverse health effects. 10 During a fire, the inhalation of toxic gases produced from burning materials is a major cause of injury and death. According to death certificates dated between 1979 and 2007 in the United Kingdom, for home fire deaths, there were eight smoke inhalation deaths for every one death from burns.…”
Section: Introductionmentioning
confidence: 99%
“…Presence of these chemicals in the environment contributes to chemical loads in wastewater, rivers, and the natural environment 9 . Recent evidence shows that exposure of nonhalogenated organophosphate components increased exposure risks and lead to adverse health effects 10 …”
Section: Introductionmentioning
confidence: 99%